Prevalence of Campylobacter Species in Diarrheal Samples of Children Less than 10 Years - Ghada N. Khalaf 1 , Thaanaa R. Abdulrahman² (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Campylobacter spp. is one of the most common causes of diarrheal diseases all over theworld, with a rapid acquisition of antibiotic resistance.Objective: Detect the frequency of Campylobacter species in diarrheal stool of children under ten years byconventional and molecular methods, and detect the bacterial ability to produce biofilm.Methods: A total of 200 children presented with diarrhea had been enrolled in this study. Campylobacterwas isolated and diagnosed primarily by characteristic features on Gram stain, culture media, biochemicaltests, and tested against 13 antibiotics by disc diffusion method. The ability of biofilm production wastested by crystal violet quantitative ELISA microtiter plate assays. Then Campylobacter spp was detectedby Multiplex PCR using species specific genes.Result: The prevalence of Campylobacter spp. was 17% by conventional methods and 15% by molecularmethod. The results of antibiotic susceptibility test showed that, there is complete resistance (100%)to cephalothin, ampicillin, and clindamycin for both species, full resistance (100%) to trimethoprimsulfamethoxazol and erythromycin by C.coli, and high resistance (92.3%) to trimethoprim-sulfamethoxazoland erythromycin by C.jejuni, while the lowest resistance was to nalidixic acid and amikacin (7.7%) byC.jejuni, and (12.5%) to tetracyclin, amoxicillin, amikacin, chloramphenicol, and ciprofloxacin by C.coli.The frequency of biofilm production in all positive Skirrow’s culture was (35.29%) as 12 out of 34 positiveisolates, ranging from mild to severe biofilm formation. By PCR assay, 64.7 % (22 of 34) positive Skirrow’sculture were also positive based on hipO gene specific for C.jejuni, while the prevalence of asp gene was(23.5%).Conclusion: The prevalence of Campylobacter spp. was 17% by conventional methods and 15% by molecularmethods, most of Campylobacter jejuni and Campylobacter coli isolates were MDR, and sensitive only tolimited number of antibiotics, many Campylobacter isolates produce biofilm, there was highly significantcorrelation between hippurate hydrolysis results and molecular detection of Campylobacter spp. dependingon hipO and asp genes.